Implementasi Fatwa DSN-MUI dalam Perlindungan Aset Investor di Pasar Modal Syariah: Analisis Prinsip Syariah dan Kaidah Fiqih PSada Mekanisme Dana Perlindungan Pemodal (DPP) - Setiawan Bin Lauri; Muhammad Rizqi Rifai (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyse the role of the Islamic capital market in supporting an investment ecosystem that complies with Sharia principles, with a focus on the mechanism of investor asset protection through the Investor Protection Fund (Dana Perlindungan Pemodal, DPP) based on DSN-MUI Fatwa No. 157/DSN-MUI/VII/2024. The research method employed is descriptive qualitative analysis with an Islamic legal approach, examining the legal basis, Islamic capital market instruments, and the Sharia principles underpinning the management of the DPP. The findings indicate that the Islamic capital market plays a significant role in creating a fair, transparent, and Sharia-compliant investment environment. DSN-MUI Fatwa No. 157/DSN-MUI/VII/2024 provides clear legal guidance on the management of the DPP, applying the principles of wakalah bil ujrah and kafalah as forms of guarantee for investors. This research also identifies that the application of qawaid fiqhiyyah, such as the principle that preventing harm takes precedence over obtaining benefit, forms the basis for DPP management to prevent injustice and misuse of assets. The implication of this research is the importance of strict supervision by authorities such as the Financial Services Authority (OJK) and DSN-MUI to ensure compliance with Sharia principles, thereby enhancing public trust in the Islamic capital market and fostering sustainable economic stability.